Odor, Not Performance, Dictates Bemisia tabaci's Selection between Healthy and Virus Infected Plants - Chen, Gong; Su, Qi; Shi, Xiaobin; Liu, Xin; Peng, Zhengke; Zheng, Huixin; Xie, Wen; Xu, Baoyun; Wang, Shaoli; Wu, Qingjun; Zhou, Xuguo; Zhang, Youjun (Frontiers in Physiology, 2017)
Although insect herbivores are generally thought to select hosts that favor the fitness of their progeny, this “mother-knows-best” hypothesis may be challenged by the presence of a plant virus. Our previous study showed that the whitefly, Bemisia tabaci, the obligate vector for transmitting Tomato yellow leaf curl virus (TYLCV), preferred to settle and oviposit on TYLCV-infected rather than healthy host plant, Datura stramonium. The performances of B. tabaci larvae and adults were indeed improved on virus-infected D. stramonium, which is consistent with “mother-knows-best” hypothesis. In this study, B. tabaci Q displayed the same preference to settle and oviposit on Tomato spotted wilt virus (TSWV)-infected host plants, D. stramonium and Capsicum annuum, respectively. As a non-vector of TSWV, however, insect performance was impaired since adult body size, longevity, survival and fecundity were reduced in TSWV infected D. stramonium. This appears to be an odor-mediated behavior, as plant volatile profiles are modified by viral infection. Infected plants have reduced quantities of o-xylene and α-pinene, and increased levels of phenol and 2-ethyl-1-hexanol in their headspace. Subsequent behavior experiments showed that o-xylene and α-pinene are repellant, while phenol and 2-ethyl-1-hexanol are attractive. This indicates that the preference of B. tabaci for virus-infected plants is modulated by the dynamic changes in the volatile profiles rather than the subsequent performances on virus-infected plants.